Residential child care : collaborative practice - Milligan, Ian, 1954- (Sage Publications, 2006)
T̀his excellent book faces the difficulties of residential child care with integrity. The emphasis on collaboration is both timely and important since it is a major theme in the training of social workers in the UK, where this book will be a valuable resource' - Andrew Hill, University of York. Residential Child Care is an innovative book which addresses the specific context of modern residential child care whilst promoting collaborative practice within a wider social work setting. The book analyses the collaborative role of organisations, field workers, parents, teachers, and children, and st.